Blockchain technology for ecological and environmental applications - Anuradha Yadav,; Shivani Shivani,; Vijaya Kittu Manda,; Vikramaditya Sangwan,; Demkiv, Anna (Ecological Questions, 2024)
This research study examines the use of Blockchain technology for ecological and environmental applications. The study presents a conceptual view aided by a literature survey to identify three major Blockchain themes connecting with the research topic - Transparency and Traceability, Conservation and Incentives, and Data Management and Monitoring. The goal of the study is to use the features offered by Blockchain Technology for sustainability, ecology, and environmental applications. As this research shows, technology can help in conservation and incentive practices such as conservation finance, tokenized rewards for ecosystem services, and rewards for sustainable practices. Blockchain has good data management and monitoring practices that can help secure environmental data, monitor various environmental parameters in real time, and provide a decentralized platform/infrastructure for environmental data analytics. Findings from this study can help environmental practitioners and researchers, research bodies, and Governmental agencies keen to use technology to preserve ecology and the environment and encourage sustainable practices.